2018
DOI: 10.1021/acs.jpcc.8b06162
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of NaPO3–AlF3 Glasses by High-Resolution Double-Resonance Nuclear Magnetic Resonance Spectroscopy

Abstract: The local structure of the model glasses (NaPO 3 ) 1−x -(AlF 3 ) x (0 ≤ x ≤ 0.4), prepared by standard melt-cooling, was extensively investigated by high-resolution solidstate nuclear magnetic resonance (NMR) including advanced double-resonance techniques. This glass system offers the opportunity of studying five different heteronuclear distance correlations (Na−F, Na−P, P−F, Al−F, and P−Al) by 10 distinct double-resonance experiments, involving all of the constituent elements present. 27 Al MAS-NMR data indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 49 publications
10
38
0
Order By: Relevance
“…Given the low intensities of Al [5] and Al[4] coordinations, integration was fixed to a chemical shift range based on the 60NaPO 3 -40AlF 3 sample, shown in Figure 5; our final values are given in Table 6. These values agree with the descriptions reported elsewhere on this same glass series: Bradtmüller et al (2018) demonstrate that at low AlF 3 content, all the aluminum is 6-fold coordinated and only at high amounts of AlF 3 (40 mol%) are small amounts of 5-fold (8%) and 4-fold (1%) aluminum present. Similarly, Brow (Brow, 1992) observed only one central peak at −10 ppm in the 27 Al NMR spectra of this glass series, without any evidence for Al [4] or Al [5].…”
Section: Structure Determinationsupporting
confidence: 92%
See 4 more Smart Citations
“…Given the low intensities of Al [5] and Al[4] coordinations, integration was fixed to a chemical shift range based on the 60NaPO 3 -40AlF 3 sample, shown in Figure 5; our final values are given in Table 6. These values agree with the descriptions reported elsewhere on this same glass series: Bradtmüller et al (2018) demonstrate that at low AlF 3 content, all the aluminum is 6-fold coordinated and only at high amounts of AlF 3 (40 mol%) are small amounts of 5-fold (8%) and 4-fold (1%) aluminum present. Similarly, Brow (Brow, 1992) observed only one central peak at −10 ppm in the 27 Al NMR spectra of this glass series, without any evidence for Al [4] or Al [5].…”
Section: Structure Determinationsupporting
confidence: 92%
“…Although the four peaks overlap, the area fractions show the expected monotonic exchange between the Q n species with and without aluminum neighbors. Moreover, the trends match those of Bradtmüller et al (2018) found for the same glass series, including the increase and then subsequent decrease of the Q 1 0Al species. The exact fitting 31 P NMR parameters can be found in Table 2.…”
Section: Structure Determinationsupporting
confidence: 80%
See 3 more Smart Citations